Photosynthesis in Plants and Algae - Häder, Donat-Peter (Anticancer Research, 2022)
Photosynthesis is the basis of almost all life on Earth. In addition to providing energy, plants and algae provide a plethora of secondary substances useful in the treatment of a number of illnesses including a wide array of cancer maladies. The first organisms on Earth used chemosynthesis for their energy needs. Photosynthetic bacteria utilize one of two different photosystems whereas cyanobacteria, eukaryotic algae and plants combine two photosystems in a linear electron transport chain. Accessory pigments such as various chlorophylls, carotenoids and phycobilins absorb the energy of impinging photons and funnel it to the reaction centers (P680 in photosystem II and P700 in photosystem I). Water is split photochemically, electrons are transported to reduce NADPH, oxygen is discarded as waste product, and protons accumulate inside the thylakoid vesicles in the chloroplasts. The resulting electrochemical gradient across the membrane is used to drive an ATPase. The produced ATP and NADPH+H+ are utilized in the Calvin cycle to fix CO2 and to produce fructose.
CRIS-Team Scopus Importer:2022-10-21
Keywords: algae; ATPase; Calvin cycle; chlorophyll; cyanobacteria; electron transport chain; Photosynthesis; photosynthetic bacteria; plants